2000
DOI: 10.1161/01.res.87.6.474
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Coupling Between Endothelial Cells and Smooth Muscle Cells in Hamster Feed Arteries

Abstract: Endothelial cells (ECs) govern smooth muscle cell (SMC) tone via the release of paracrine factors (eg, NO and metabolites of arachidonic acid). We tested the hypothesis that ECs can promote SMC relaxation or contraction via direct electrical coupling. Vessels (resting diameter, 57+/-3 microm; length, 4 mm) were isolated, cannulated, and pressurized (75 mm Hg; 37 degrees C). Two microelectrodes were used to simultaneously impale 2 cells (ECs or SMCs) in the vessel wall separated by 500 microm. Impalements of on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
364
3
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 279 publications
(391 citation statements)
references
References 49 publications
23
364
3
1
Order By: Relevance
“…For example, in hamster retractor muscle arterioles, a more pronounced myoendothelial coupling was evident in acetylcholine-treated arteries than in arteries in which either smooth muscle or endothelial cells were stimulated by the injection of a negative current. 5 In the present study, we observed that the endothelial cell uncoupling observed 5 to 10 minutes after cell stimulation with either bradykinin or 11,12-EET was not detectable in cells pretreated with inhibitors of MEK, which prevent the activation of ERK1/2. Both bradykinin and 11,12-EET activated ERK1/2 in endothelial cells 30,31 and induced a MEK inhibitor-sensitive shift in the mobility of Cx43 in SDS-PAGE, changes that are indicative of Cx43 phosphorylation.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…For example, in hamster retractor muscle arterioles, a more pronounced myoendothelial coupling was evident in acetylcholine-treated arteries than in arteries in which either smooth muscle or endothelial cells were stimulated by the injection of a negative current. 5 In the present study, we observed that the endothelial cell uncoupling observed 5 to 10 minutes after cell stimulation with either bradykinin or 11,12-EET was not detectable in cells pretreated with inhibitors of MEK, which prevent the activation of ERK1/2. Both bradykinin and 11,12-EET activated ERK1/2 in endothelial cells 30,31 and induced a MEK inhibitor-sensitive shift in the mobility of Cx43 in SDS-PAGE, changes that are indicative of Cx43 phosphorylation.…”
Section: Discussionsupporting
confidence: 41%
“…[3][4][5][6] However, there has been no convincing demonstration of a direct link between dynamic alterations in myoendothelial gap junctions and relaxation/vasodilatation.…”
mentioning
confidence: 99%
“…Stimulation of endothelial cells can also produce smooth muscle cell hyperpolarization through release of autacoids that activate K ϩ channels in smooth muscle (12). Furthermore, the conduction of vasodilation can attenuate sympathetic vasoconstriction (45), with hyperpolarization initiated and conducted along the endothelium and into the surrounding smooth muscle cells through myoendothelial gap junctions (23,78). These signaling pathways provide alternative mechanisms through which exerciseinduced increases in metabolites and blood flow can influence smooth muscle contraction.…”
Section: Mechanisms Underlying Functional Sympatholysismentioning
confidence: 99%
“…Gap junctions are formed by the docking of two connexin subunits, each made up of six connexin proteins arranged around a central core [13], which creates a channel allowing the direct exchange of ions and lowmolecular-weight molecules [13]. Conduction studies have indicated that gap junctions between endothelial cells may be involved in the propagation of the EDHF response downstream along the vessel [14,15], and EDHF-attributed hyperpolarisations also propagate from endothelial cells through the entire smooth muscle layer via gap junctions, with a current that spreads with negligible attenuation [16].…”
Section: Introductionmentioning
confidence: 99%